Enhanced chondrogenesis of bone marrow-derived stem cells by using a combinatory cell therapy strategy with BMP-2/TGF-β1, hypoxia, and COL1A1/HtrA1 siRNAs - Florence Legendre (Nature Portfolio, 2017)
Abstract Mesenchymal stem cells (MSCs) hold promise for cartilage engineering. Here, we aimed to determine the best culture conditions to induce chondrogenesis of MSCs isolated from bone marrow (BM) of aged osteoarthritis (OA) patients. We showed that these BM-MSCs proliferate slowly, are not uniformly positive for stem cell markers, and maintain their multilineage potential throughout multiple passages. The chondrogenic lineage of BM-MSCs was induced in collagen scaffolds, under normoxia or hypoxia, by BMP-2 and/or TGF-β1. The best chondrogenic induction, with the least hypertrophic induction, was obtained with the combination of BMP-2 and TGF-β1 under hypoxia. Differentiated BM-MSCs were then transfected with siRNAs targeting two markers overexpressed in OA chondrocytes, type I collagen and/or HtrA1 protease. siRNAs significantly decreased mRNA and protein levels of type I collagen and HtrA1, resulting in a more typical chondrocyte phenotype, but with frequent calcification of the subcutaneously implanted constructs in a nude mouse model. Our 3D culture model with BMP-2/TGF-β1 and COL1A1/HtrA1 siRNAs was not effective in producing a cartilage-like matrix in vivo. Further optimization is needed to stabilize the chondrocyte phenotype of differentiated BM-MSCs. Nevertheless, this study offers the opportunity to develop a combinatory cellular therapy strategy for cartilage tissue engineering.